Finite element model of machining with high pressure coolant for Ti-6Al-4V alloy - Mohd Hadzley, Abu Bakar, Dr.; Raja Izamshah, Raja Abdullah, Dr.; Siti Sarah, A.; Nurul Fatin, Mohamad Raffi (Malaysian Technical Universities Network (MTUN), 2013)
Malaysian Technical Universities Conference on Engineering and Technology (MUCET) 2012 organised by technical universities under the Malaysian Technical Universities Network (MTUN), 20th - 21st November 2012 at Hotel Seri Malaysia, Kangar, Perlis.